Landau-Zener transitions in the presence of harmonic noise - Kraft, Matthias; Burkhardt, Stephan; Mannella, Riccardo; Wimberger, Sandro (Fluctuation and noise letters, 2013)
We study the influence of off-diagonal harmonic noise on transitions in a Landau-Zener model. We demonstrate that the harmonic noise can change the transition probabilities substantially and that its impact depends strongly on the characteristic frequency of the noise. In the underdamped regime of the noise process, its effect is compared with the one of a deterministic sinusoidally oscillating function. While altering the properties of the noise process allows one to engineer the transitions probabilities, driving the system with a deterministic sinusoidal function can result in larger and more controlled changes of the transition probability. This may be relevant for realistic implementations of our model with Bose-Einstein condensates in noise-driven optical lattices.
Gesehen am 30.03.2021